The Role of a Professional Society in Broadening Participation in Science: A National Model for Increasing Persistence. (18th July 2018) - Mourad, Teresa M; McNulty, Amy Fox; Liwosz, Desiree; Tice, Karin; Abbott, Frederick; Williams, Gwendolyn C; Reynolds, Julie A
Abstract: Professional societies can, and should, recruit and retain young scientists by providing a welcoming and inclusive intellectual home. SEEDS (Strategies for Ecology Education, Diversity and Sustainability), the flagship education program of the Ecological Society of America, is designed to broaden participation in ecology through mentoring, field trips, leadership development, and research fellowships. Nationally, fewer than 40% of college students who intended to pursue a career in science, technology, math, or engineering complete their degrees in these fields, and these numbers are even smaller for underrepresented minorities (URMs). In contrast, 80% of SEEDS alumni in our study had completed at least one degree in an ecology-related field, and the completion rate for URMs was 85%. In addition, 71% of working SEEDS alumni respondents have careers in ecology. SEEDS is a model for other professional societies wishing to increase students' self-efficacy and sense of belonging through professional development and positive social reinforcement.